2015
DOI: 10.1007/s00128-015-1687-1
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Pyrene onto the Agricultural By-Product: Corncob

Abstract: The adsorption behavior of pyrene on corncob was studied to provide a theoretical basis for the possible use of this material as an immobilized carrier for improving the bioremediation of PAH-contaminated soil. The results were as follows. Kinetic experiments showed that the adsorption processes obeyed a pseudo-second-order model. The intraparticle diffusion of Weber-Morris model fitting showed that the film and intraparticle diffusions were the key rate-limiting processes, and the adsorption process mainly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In a study, it was found that their volatility decreased as the number of benzene rings increased, the solubility in fat increased, and the difficulty of environmental degradation increased. Due to their high level of carcinogenicity, teratogenicity, mutagenicity, and ecological toxicity [69], aromatic compounds-which are typically present in water, soil, and sediments [68]-pose a severe risk to human health and the environment [74]. Nocardioides has been found to degrade aromatic compounds such as 2-dinitroanisole, ibuprofen, dibenzofuran, and nitrophenol.…”
Section: The Degradation Of Aromatic Compoundsmentioning
confidence: 99%
“…In a study, it was found that their volatility decreased as the number of benzene rings increased, the solubility in fat increased, and the difficulty of environmental degradation increased. Due to their high level of carcinogenicity, teratogenicity, mutagenicity, and ecological toxicity [69], aromatic compounds-which are typically present in water, soil, and sediments [68]-pose a severe risk to human health and the environment [74]. Nocardioides has been found to degrade aromatic compounds such as 2-dinitroanisole, ibuprofen, dibenzofuran, and nitrophenol.…”
Section: The Degradation Of Aromatic Compoundsmentioning
confidence: 99%
“…Moreover, the values of C (17.94 and 40.18) calculated by intra–particle diffusion model were all greater than 0. These results indicated that intra–particle diffusion is not the sole rate–limiting step, other kinetic models may also govern the adsorption rate, or multiple rate–controlled steps may manipulate concurrently together [47] …”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that intra-particle diffusion is not the sole rate-limiting step, other kinetic models may also govern the adsorption rate, or multiple rate-controlled steps may manipulate concurrently together. [47]…”
Section: Samplementioning
confidence: 99%
“…The plot of q t versus t 1/2 at different initial Li + concentration is shown in Figure , and the corresponding k calculated from the plot is also listed in Table . On the basis of the Weber‐Morris model, the plot of q t versus t 1/2 should show a linear if intraparticle diffusion is included in the adsorption process. Besides, if these lines pass through the origin, which indicated intraparticle diffusion is the rate controlling step .…”
Section: Resultsmentioning
confidence: 99%